2022
DOI: 10.3390/molecules27217617
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Co-Mo-B Film: A High-Active Electrocatalyst for Hydrogen Generation in Alkaline Seawater

Abstract: The development of efficient electrochemical seawater splitting catalysts for large-scale hydrogen production is of great importance. In this work, we report an amorphous Co-Mo-B film on Ni foam (Co-Mo-B/NF) via a facile one-step electrodeposition process. Such amorphous Co-Mo-B/NF possesses superior activity with a small overpotential of 199 mV at 100 mA cm−2 for a hydrogen evolution reaction in alkaline seawater. Notably, Co-Mo-B/NF also maintains excellent stability for at least 24 h under alkaline seawater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(28 citation statements)
references
References 58 publications
1
27
0
Order By: Relevance
“…The corresponding Tafel slope in Figure e derived from LSV curves indicates faster reaction kinetics for FeVO­(OH)/NiMoW­(OH) 2 , with a small Tafel slope value of 67 mV/dec as compared with FeVO­(OH) (80 mV/dec) and NiMoW­(OH) 2 (115 mV/dec). At high current density, as shown in Figure f, FeVO­(OH)/NiMoW­(OH) 2 exhibits the lowest overpotential of 280 mV @ 100 mA/cm 2 , which could be attributed to the synergistic effect and increase in the catalytically active surface area. , …”
Section: Resultsmentioning
confidence: 91%
“…The corresponding Tafel slope in Figure e derived from LSV curves indicates faster reaction kinetics for FeVO­(OH)/NiMoW­(OH) 2 , with a small Tafel slope value of 67 mV/dec as compared with FeVO­(OH) (80 mV/dec) and NiMoW­(OH) 2 (115 mV/dec). At high current density, as shown in Figure f, FeVO­(OH)/NiMoW­(OH) 2 exhibits the lowest overpotential of 280 mV @ 100 mA/cm 2 , which could be attributed to the synergistic effect and increase in the catalytically active surface area. , …”
Section: Resultsmentioning
confidence: 91%
“…Borides/carbides are mainly the active sites for the HER, and oxides/(oxy) hydroxides formed during the OER process are mainly the OER active sites. 52,150,151 Hence, B and C doping are also effective to enhance the catalytic performance of bulk Fe-based alloys. Guo et al 152 used amorphous boron, potassium uoroborate, and silicon carbide as boronization agents to treat metal sheets (Ni, Co, Fe, NiFe, and 304 steel) (Fig.…”
Section: Dopingmentioning
confidence: 99%
“…The development of efficient and commercially viable catalysts for the hydrogen evolution reaction (HER), and the focus on non-precious group compounds and carbon-supported catalyst, especially MoS 2 in an acidic aqueous solution toward the HER, spurred the interest of scientists to probe deeper the nature of the active sites and to improve the efficiency of this transition metal dichalcogenide. Detailed structure–activity investigations revealed that the edges of MoS 2 sheets are the active sites for the HER, with some contributions from basal defect sites and grain boundary sites. , Crystalline MoS 2 has three distinct phases, namely, tetragonal (1T), hexagonal (2H), and rhombohedral (3R), where the digit denotes the number of MoS 2 layers per unit cell.…”
Section: Introductionmentioning
confidence: 99%